2015
DOI: 10.1136/bmjspcare-2014-000819
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of meditative interventions for informal caregivers and health professionals

Abstract: Background Burnout, stress and anxiety have been identified as areas of concern for informal caregivers and health professionals, particularly in the palliative setting. Meditative interventions are gaining acceptance as tools to improve well-being in a variety of clinical contexts, however, their effectiveness as an intervention for caregivers remains unknown. Aim To explore the effect of meditative interventions on physical and emotional markers of well-being as well as job satisfaction and burnout among i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 47 publications
5
65
1
8
Order By: Relevance
“…Studies on employee burnout have focused mainly teachers, nurses, informal caregivers and general practitioners exploring rates of burnout and the effectiveness of a range of interventions including meditation and related approaches such as mindfulness (e.g. Dharmawardene, Givens, Wachholtz, Makowski, & Tjia, 2016;Federici & Skaalvik, 2012;Shirom et al, 2013). Some research has also explored burnout in mental health professionals (MHP) including psychiatrists, non medical MHPs and psychiatric trainees indicating high levels of burnout possibly due to issues such as working with demanding or violent patients, low pay, lack of positive feedback, working with little training or experience, high job responsibility and patient suicides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on employee burnout have focused mainly teachers, nurses, informal caregivers and general practitioners exploring rates of burnout and the effectiveness of a range of interventions including meditation and related approaches such as mindfulness (e.g. Dharmawardene, Givens, Wachholtz, Makowski, & Tjia, 2016;Federici & Skaalvik, 2012;Shirom et al, 2013). Some research has also explored burnout in mental health professionals (MHP) including psychiatrists, non medical MHPs and psychiatric trainees indicating high levels of burnout possibly due to issues such as working with demanding or violent patients, low pay, lack of positive feedback, working with little training or experience, high job responsibility and patient suicides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Through educational interventions, mediation, or interventions focused on affected individuals, treatment of burnout among nurses has been studied, although results have been limited. [10][11][12] In the last decade, numerous burnout risk factors have been studied among nursing professionals, such as work experience, 13 job satisfaction, 14 personality, and sociodemographic factors. 4 Another important risk factor that has been assessed in recent studies 15,16 is the hospital unit or specialty in which nurses work.…”
mentioning
confidence: 99%
“…In spite of the diversification of protocols and methods, these experiences have shown benefits to these individuals' health. 11,22 The reduction in anxiety observed in the two groups of the present study is justified, naturally, by the coping strategies employed by the individuals to overcome stressful situations. The volunteers' preponderant attachment to seeking religious practices and wishful thinking represents the manifestation of their impotence to control the clinical response of their children and adolescents undergoing treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Although these trials are still incipient, they have shown benefits to the health of caregivers of individuals in different health conditions. 11,12 We have not found a study in the literature that assesses the effects of this practice on the population of caregivers of children and adolescents with cancer.…”
Section: Introductionmentioning
confidence: 99%